2017
DOI: 10.3892/mmr.2017.8183
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract from Cnidium monnieri (L.) Cusson induces cell cycle arrest and apoptosis via regulation of the p53‑independent pathway in HepG2 and Hep3B hepatocellular carcinoma cells

Abstract: Cnidium monnieri (L.) Cusson is a frequently used traditional Chinese medicine that treats gynecological diseases and carbuncles. However, the mechanism of action of C. monnieri remains to be fully elucidated. The present study examined the cell cycle arrest and apoptotic effects resulting from ethanol extract of C. monnieri (CME) in HepG2 (wild‑type p53) and Hep3B (p53‑null) hepatocellular carcinoma cells. An MTT assay was used to confirm the anti‑proliferative effect of CME. The cells were stained with Hoech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…Cnidium monnieri (L.) Cusson (CME) is a frequently used Chinese herbal medicine that treats gynecological diseases and carbuncles. A recent study showed the cell cycle alteration and apoptosis of HepG2 (wildtype p53) and Hep3B (p53null) by ethanol extract of CME, suggesting that CME induced G1 arrest and apoptosis via the Akt/GSK3β signaling pathway [57].…”
Section: Functional Roles Of Chinese Medicine Extracts and Fractions mentioning
confidence: 99%
“…Cnidium monnieri (L.) Cusson (CME) is a frequently used Chinese herbal medicine that treats gynecological diseases and carbuncles. A recent study showed the cell cycle alteration and apoptosis of HepG2 (wildtype p53) and Hep3B (p53null) by ethanol extract of CME, suggesting that CME induced G1 arrest and apoptosis via the Akt/GSK3β signaling pathway [57].…”
Section: Functional Roles Of Chinese Medicine Extracts and Fractions mentioning
confidence: 99%
“…Agilent 6530 Accurate-Mass Q-TOF LC/MS system (Agilent Technologies, Santa Clara, CA) was equipped with an electrospray ionization (ESI); MS data were acquired across the range m/z 100-1500 in positive and negative ion modes. e operating conditions were as follows: nitrogen as dry gas with temperature at 325°C and flow rate at 5.0 L/min, and sheath gas with temperature at 400°C and flow rate at 12 20 rats were randomly divided into HXHJ group (n � 10) and control group (n � 10). e HXHJ group was treated by intragastric administration of HXHJ (2.44 g/kg) twice a day for 3 days.…”
Section: Mass Spectrometry Conditionsmentioning
confidence: 99%
“…To examine cell apoptosis, the Hoechst 33342 staining assay was performed as previously reported [12] with minor revision. HepG2 cells were seeded into 6-well plates for 12 h and then treated with different concentrations of PE for 24 h. Subsequently, the culture medium was removed and the HepG2 cells were stained with Hoechst 33342 (final concentration 1.0 mg/mL) for 20 min, the apoptotic cell changes in morphology such as chromatin condensation and nuclear shrinking could be characterized.…”
Section: Hoechst Stainingmentioning
confidence: 99%
“…Tutin of Apiaceae is the only representative of the Cnidium species in Turkey, and is known as "galyabişotu" (Yüzbaşıoğlu et al, 2018). Previous Cnidium studies reported acaricidal, antioxidant, antipruritic, anticancer, hepatoprotective, and anti-inflammatory activities (Oh et al, 2002;Jeong et al, 2009;Li et al, 2015;Hong et al, 2017;Lim et al, 2018;Tran et al, 2018;Kim et al, 2018). However, there are only a few previous reports on the essential oil (EO) compositions,where aerial parts were investigated in two different studies (Kapetanos et al, 2008;Polat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%